KV10.1 potassium channels in cancer - Pardo, Luis (Henry Stewart Talks, 2011)
Ion channels with relevant roles in oncology, Kv10.1. Structure and expression profile, Aberrant expression of KV10.1 in cancer cells, Prognostic values of KV10.1 expression, Therapeutic approaches using KV10.1 as target, Functional antibodies against KV10.1 and their potential in oncology
Archived at 2023/11/30